Tricuspid surgery at the time of LVAD implant: A critique - Hoopes, Charles (Frontiers in Cardiovascular Medicine, 2022)
Tricuspid regurgitation (TR) is a common finding in patients with end stage heart failure referred for implantation of left ventricular assist devices. While functional TR frequently resolves after left ventricular unloading, patients with residual and progressive TR demonstrate increased rates of RV dysfunction and poor survival. Criteria for intervention on the tricuspid valve have focused on the degree of tricuspid annular dilatation and the severity of tricuspid regurgitant volume. The surgical decision making regarding intervention on the tricuspid valve remains obscure and historical cohort data cannot distinguish cause from effect.